Femtosecond laser pumped by coherent polarization locked diode. - Purnawirman. (2012)
We developed coherent polarization locking technique that significantly improves the brightness of the diode bar, which in turn is used to pump solid state bulk laser to obtain low-cost femtosecond laser source. The coherent locking consists of external cavity that combines emissions from arrays of emitters in the diode bar while their phases are passively locked via polarization discrimination. By designing a cavity with spatial filter, we demonstrated single mode coherently locked laser diode with maximum power of 1 W. We further scaled the power to more than 7.2 W by designing a cavity that combines multimode emissions from the emitters while compensating the smile effect by retro-reflector configuration. Both laser systems demonstrated brightness improvement over an order of magnitude compared to the conventional diode bar. We obtained 2.35 ps pulse width of 18 mW average power from Er, Yb: Glass laser by using single mode coherently locked diode. From the multimode coherently locked diode, we obtained 177 fs pulse width and 0.55 W average power of Yb: KYW laser.